2017
DOI: 10.1155/2017/5410143
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Corneal Young’s ModulusIn VivoBased on a Fluid-Filled Spherical-Shell Model with Scheimpflug Imaging

Abstract: Current intraocular pressure (IOP) measurement using air puff could be erroneous without applying proper corrections. Although noncontact tonometry is not considered to be accurate, it is still popularly used by eye clinics. It is thus necessary to extract the correct information from their results. This study proposes a practical approach to correctly measure IOP in vivo. By embedding a new model-based correction to the Corvis® ST, we can extract the corneal Young's modulus from the patient data. This Young's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…The basic mechanical parameters are Young´s modulus and Poisson´s ratio. Young´s modulus ranges from 0.054 to 0.359 MPa, Poisson´s ratio has the constant value of 0.48 [16,17]. The average value of Young´s modulus (0.207 MPa) was applied in our mechanical model proposed in [15].…”
Section: Fig 1 Basic Geometrical Parameters Of Corneamentioning
confidence: 99%
“…The basic mechanical parameters are Young´s modulus and Poisson´s ratio. Young´s modulus ranges from 0.054 to 0.359 MPa, Poisson´s ratio has the constant value of 0.48 [16,17]. The average value of Young´s modulus (0.207 MPa) was applied in our mechanical model proposed in [15].…”
Section: Fig 1 Basic Geometrical Parameters Of Corneamentioning
confidence: 99%
“…Subsequently, on the basis of the corneal pressure distribution results and average size of >64 group's corneal edge-of-arc (r = 6.432 mm, RAD = 0.423 mm) [8,9], this study simulated the contact surface of RGP lenses for individuals older than 64 years by using ANSYS HFSS ® to improve the contact stress. By comparing Figures 10 and 11, we found that the stress concentration area before using the decompression design was higher than that after using the decompression design.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the IOP value (Table 1), Young's modulus, and Poisson's ratio of the cornea was adopted from a study by Shin et al [8]. They collected IOP samples from 536 healthy individuals from 2012 to 2016, and confidence interval (CI) for each age group was 95%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations